Motivational drivers of customer brand engagement and its effect on share of wallet in a social media context - Tiensuu, Severi (2014)
In recent years, many companies have used social media as part of their marketing and brand building activities. The rise of social media has strengthened the need for customer activation and engagement. Customer brand engagement offers companies multiple positive outcomes, such as satisfaction, trust, loyalty, and empowerment, which potentially facilitate successful business performance. The idea of engagement is relatively new in the marketing literature, and academic research has only minimally examined the potential for growth presented by engaging customers. However, numerous researchers have recognized the growing academic interest in customer brand engagement, as evidenced by the Marketing Science Institute’s (MSI) highlighting of customer engagement as one of its key research priorities. Another issue of increasing importance in the marketing literature is share of wallet (SOW), which pertains to the share of a customer's expenses on a product that goes to the firm selling the product. The connection between engagement and SOW has been insufficiently examined, thereby preventing a thorough understanding of this relationship. This study presents four frequently found motivational drivers of customer brand engagement, community, information and enjoyment, identity and economics and examines the nature of the relationship between these drivers and engagement. This study also analyzes how perceived consumer innovativeness moderates the relationship between engagement and SOW. Results suggest that community exerts the strongest positive effect on customer brand engagement and that such engagement positively influences SOW. The findings also indicate that perceived consumer innovativeness positively affects the relationship between engagement and SOW. Furthermore, a positive relationship exists between frequency of visits and SOW. This study enhances the understanding of customer brand engagement by describing the nature of this strategy and combines engagement and SOW theories to develop a perspective on the association between the two.